2017
DOI: 10.1519/jsc.0000000000002058
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Musculoskeletal Movement Assessment Tools: A Systematic Review and Critical Appraisal of Their Development and Applicability to Professional Practice

Abstract: Multicomponent movement assessment tools have become commonplace to measure movement quality, proposing to indicate injury risk and performance capabilities. Despite popular use, there has been no attempt to compare the components of each tool reported in the literature, the processes in which they were developed, or the underpinning rationale for their included content. As such, the objective of this systematic review was to provide a comprehensive summary of current movement assessment tools and appraise the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…While many believe that movement competency is linked to injury risk and/or performance (where movement competency is defined using conventional a priori definition such as torso is parallel with the tibia when performing the deep squat), there remains little evidence supporting such connections (Gross and Battié, 2006;Mottram and Comerford, 2008;Schneiders et al, 2011;Okada et al, 2011;Parchmann and McBride, 2011). Perhaps our a priori criteria for subjectively evaluating movement competency are incorrect or incomplete (Bennett et al, 2017), or our clinical eye is simply not appropriately tuned to detect important and meaningful changes. As an alternative to this top-down approach, use of emerging tools in machine learning might help us to identify naturally-occurring movement phenotypes, where continued research can then explore phenotypes that are associated with positive or negative health outcomes with respect to specific task objectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many believe that movement competency is linked to injury risk and/or performance (where movement competency is defined using conventional a priori definition such as torso is parallel with the tibia when performing the deep squat), there remains little evidence supporting such connections (Gross and Battié, 2006;Mottram and Comerford, 2008;Schneiders et al, 2011;Okada et al, 2011;Parchmann and McBride, 2011). Perhaps our a priori criteria for subjectively evaluating movement competency are incorrect or incomplete (Bennett et al, 2017), or our clinical eye is simply not appropriately tuned to detect important and meaningful changes. As an alternative to this top-down approach, use of emerging tools in machine learning might help us to identify naturally-occurring movement phenotypes, where continued research can then explore phenotypes that are associated with positive or negative health outcomes with respect to specific task objectives.…”
Section: Introductionmentioning
confidence: 99%
“…The Functional Movement Screen TM (FMS) (Functional Movement Systems, Chatham, VA, United States) remains a popular tool for movement screening (Bennett et al, 2017). Sinden et al (2017) identified the FMS TM as one of the most commonly used approaches for movement screening among Kinesioligists.…”
Section: Introductionmentioning
confidence: 99%
“…Movement screens are developed using different methods including known pathomechanics 4 and injury mechanisms, 5 , 6 sport and fundamental movement requirements, 7 and expert opinion. 8 Three broad categories of movement screens have been reported in the literature: jump testing, balance with reaching tests, and movement quality against a standard criterion.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Balance with reaching tests, such as the Star Excursion and Y Balance Test (YBT), 12 have been used to associate poor performance with increased rate of injury in high school 13 and collegiate athletes. 14 Movement quality compared against a standard criterion has been used in multiple component assessment tools, 7 including tasks such as squatting, balance, lunge, push-up, and arm movement. These include the foundation matrix, 15 batteries of different movements, 16 and the movement competency screen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation